(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
The aim of the study was to compare the yield, nature and antimicrobial activity of nanoparticles synthesized using Calotropis procera leaf extract. ZnO NPs synthesized were characterized by FTIR and SEM. It was evident from SEM images that the size of the particles obtained by biological method is ranging from 100-200 nm. Antibacterial study was carried out on human bacterial and plant bacterial pathogens and their MIC values were determined. The antibacterial activity towards human bacterial and plant pathogen showed good sensitivity towards the green synthesized ZnO NP’s at all concentrations and maximum zone of inhibition occurred at the concentration of 30μg/mL. Minimum Inhibitory concentrations of NPs against human pathogenic bacteria and plant bacterial pathogens, shows that all tested microorganisms were completely inhibited at the concentration of 50 to 12.5μg/ml of nano-ZnO. The antifungal activity of ZnO NPs against fungi shows that different concentration of ZnO nanoparticles caused significant inhibition in the spore germination.